Remittances and the Brain Drain Revisited : The Microdata Show That More Educated Migrants Remit More - Bollard, Albert (World Bank, 2013)
Two of the most salient trends in migration and development over the last two decades are the large rise in remittances and in the flow of skilled migrants. However, recent literature based on cross-country regressions has claimed that more educated migrants remit less, leading to concerns that further increases in skilled migration will impede remittance growth. Microdata from surveys of immigrants in 11 major destination countries are used to revisit the relationship between education and remitting behavior. The data show a mixed pattern between education and the likelihood of remitting, and a strong positive relationship between education and amount remitted (intensive margin), conditional on remitting at all (extensive margin). Combining these intensive and extensive margins yields an overall positive effect of education on the amount remitted for the pooled sample, with heterogeneous results across destinations. The microdata allow investigation of why the more educated remit more, showing that the higher income earned by migrants, rather than family characteristics, explains much of the higher remittances.